2022
DOI: 10.1186/s13104-022-06093-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of decomposition algorithms for identification of single motor units in ultrafast ultrasound image sequences of low force voluntary skeletal muscle contractions

Abstract: Objective In this study, the aim was to compare the performance of four spatiotemporal decomposition algorithms (stICA, stJADE, stSOBI, and sPCA) and parameters for identifying single motor units in human skeletal muscle under voluntary isometric contractions in ultrafast ultrasound image sequences as an extension of a previous study. The performance was quantified using two measures: (1) the similarity of components’ temporal characteristics against gold standard needle electromyography record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 27 publications
1
24
0
Order By: Relevance
“…Both the MRI technique and the early UUS methods use electrical stimulation to generate muscle activity to image MUs. In contrast, a recently proposed UUS technique (MU-UUS) can identify single MUs in voluntary activations using a blind source separation algorithm of the velocity image sequences to extract spatiotemporal components (Rohlén et al, 2020b) in which a subset corresponds to the MU (Carbonaro et al, 2022;Rohlén et al, 2022Rohlén et al, , 2020a. Given this, MU-UUS provides estimates of MU territories in cross-section and the corresponding train of twitches evoked by the spinal motor neurons' neural discharges (spikes).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Both the MRI technique and the early UUS methods use electrical stimulation to generate muscle activity to image MUs. In contrast, a recently proposed UUS technique (MU-UUS) can identify single MUs in voluntary activations using a blind source separation algorithm of the velocity image sequences to extract spatiotemporal components (Rohlén et al, 2020b) in which a subset corresponds to the MU (Carbonaro et al, 2022;Rohlén et al, 2022Rohlén et al, , 2020a. Given this, MU-UUS provides estimates of MU territories in cross-section and the corresponding train of twitches evoked by the spinal motor neurons' neural discharges (spikes).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies involving the MU-UUS analysis have provided estimates of unfused tetanic signals of single MUs (Ali et al, 2020;Rohlén et al, 2022Rohlén et al, , 2020bRohlén et al, , 2020a. These unfused tetanic estimates have further been used to estimate their spike trains (neural discharges).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study found that methodological improvements in velocity image separation (blind source separation, BSS) should lead to a higher identification rate 6 . A methodological improvement could include more information about the MU characteristics in the separation process 6 . The reasoning is that the current method neglects the temporal information in the separation process and focuses on sparse spatial (pixel) distributions as cost functions motivated by the physical muscle unit territories (Fig.…”
Section: Introductionmentioning
confidence: 99%